The IDRT (Indonesian Rupiah Token) Stablecoin Dilemma: Navigating the Intersection of Legal Monopolies and Islamic Ethical Norms in Digital Transactions - Al Munawar, Faishal Agil; Rizky Syaputra, Abdul Wahid (Faculty of Sharia and Law, UIN Syarif Hidayatullah Jakarta, 2025)
IDRT stablecoin is a digital financial innovation that is claimed to be a representation of the rupiah with a stable value. Although its use is increasing, the legality of IDRT in Indonesia is unclear because Law No. 7 of 2011 stipulates the rupiah as the only legal tender. In Islamic law, there is no specific fatwa regarding IDRT, thus creating uncertainty. This study uses a normative juridical approach to analyze the relationship between positive legal instruments and relevant Islamic legal views. As a result, IDRT is not recognized as a legal tender according to positive law, but meets the criteria of sil'ah (tradeable commodity) in Islamic law because it has a stable value, is supported by rupiah reserves, and is free from gharar (uncertainty), qimar (speculation), and ḍarar (harm). Through the principle of istihsan bil maslahah (juristic preference for public interest), IDRT may be conditionally accepted within a sharia-compliant framework, provided regulatory compliance is ensured. Abstrak:Stablecoin IDRT merupakan inovasi keuangan digital yang diklaim sebagai representasi rupiah dengan nilai yang stabil. Meskipun penggunaannya semakin meningkat, legalitas IDRT di Indonesia masih belum jelas karena Undang-Undang Nomor 7 Tahun 2011 menetapkan rupiah sebagai satu-satunya alat pembayaran yang sah. Dalam hukum Islam, belum ada fatwa khusus mengenai IDRT sehingga menimbulkan ketidakpastian. Penelitian ini menggunakan pendekatan yuridis normatif untuk menganalisis hubungan antara instrumen hukum positif dengan pandangan hukum Islam yang relevan. IDRT tidak diakui sebagai alat pembayaran yang sah menurut hukum positif, tetapi memenuhi kriteria sil'ah (komoditas yang dapat diperjualbelikan) dalam hukum Islam karena memiliki nilai yang stabil, didukung oleh cadangan rupiah, dan bebas dari gharar (ketidakpastian), qimar (spekulasi), dan ḍarar (bahaya). Melalui prinsip istihsan bil maslahah (keutamaan hukum untuk kepentingan umum), IDRT dapat diterima dengan syarat sesuai terhadap peraturan.